The impact of transthoracic point-of-care ultrasound on the pause time between chest compressions during cardiopulmonary resuscitation: systematic review and meta-analysis - Melo Filho, Carlos Alberto de (2023)
Objective: To value the impact of transthoracic point-of-care ultrasound (POCUS) on pause time between chest compressions during CPR. Methods: Systematic literature review in PubMed, Embase, Scopus, and Biblioteca Virtual em Saúde databases. The primary outcome of the meta-analysis was the difference in pause time between chest compressions in CPR with and without transthoracic POCUS. The secondary outcome was the return of spontaneous circulation of the manual verification and transthoracic POCUS groups. We used software R version 4.1.3 to perform all statistical analyses. Results: The search in the databases resulted in 6177 publications. However, only five met all inclusion criteria. Most of the studies were prospective cohorts. The mean age ranged from 56.5 to 66 years, and males were predominant in all studies. All showed longer pauses in the POCUS group. There was a statistical association between the use of POCUS and longer pauses between chest compressions with an MD of 3.88 (95% CI 2.76; 5.01; p-value < 0.0001). The additional exclusion of any of the five studies did not change the result, i.e., DM between the two groups continued to be statistically significant. Conclusion: The combined analysis of the data suggests that using the POCUS increases the pause time between chest compressions by an average of 3.88 seconds. However, further studies evaluating the impact on return to spontaneous circulation and mortality are necessary.